Burden of Severe Acute Malnutrition in under-five Children (2–59 Months) Admitted in a Tertiary Care Hospital of Delhi. (21st April 2017) - Mathur, Alka; Tahilramani, Geetanjali; Makhija, Sonia; Devgan, Veena
ABSTRACT: Objective: The aim of the present study is to assess the burden of severe acute malnutrition (SAM) and other malnutrition in a tertiary care hospital in Delhi. Methods: All patients aged 2–59 months admitted from August 2012 to July 2014 were screened for malnutrition by anthropometry using standard techniques, and SAM was diagnosed as per guidelines [1, 2]. Results: During the study period, 4520 children of age 2–59 months were admitted and complete data of 4354 children were available, which were analysed. Of these, 50.4% were underweight, 44.6% were stunted, 33.5% were wasted, 0.76% had oedematous malnutrition and 18.3% had SAM. Of all patients with SAM, 80% were <24 months old, with 54.1% males and 45.9% females. Moderate acute malnutrition was present in 21.4%. Associated co-morbidities were diarrhoea or respiratory infection or both. Conclusion: Hospitals of Delhi have a high load of complicated SAM and need adequate infrastructure and facilities for management of these children.